SAT0264 Influence of Exercise in Recent Onset Axial Spondyloarthritis:Results Esperanza Cohort. (9th June 2015) - Almodovar, R.; Navarro-Compán, V.; Moreno, E.; Sanz, J.; Zarco, P.
Abstract : Background: Currently, it has been seen that many of the symptoms and limitations of the spondyloarthritis (SpA) may improve with exercise. To determine the influence of exercise in our population with early axial SpA, our group decided to analyze possible differences Objectives: Analyze the existence of clinical differences, image, quality of life, work disability and treatment among patients with early axial SpA who exercise compared to those who did not. Methods: Baseline data from ESPERANZA program (<45 years old, symptoms duration 3-24 months and with inflammatory back pain -IBP- or asymmetrical arthritis or spinal/joint pain plus ≥1 SpA features) was used for a descriptive analysis. Patients fulfilling the ASAS classification criteria for axial SpA were included. Socio-demographic and disease characteristics, disease activity indices (ESR, CRP, BASDAI, BASFI), quality of life (ASQoL), imaging (total BASRI, radiographic sacroiliitis –NY criteria- and sacroiliitis on MRI -ASAS criteria-), work disability and NSAIDs treatment were compared between patients with early axial SpA who exercise compared to those who did not. The practice of physical exercise was defined as the patient confirmed in the consultation as part of your regular routine. Analysis: Chi square was used to compare rates and Student-t test to analyze continuous variables. Results: A total of 291 early axial SpA (191 men and 100 women) with a mean age of 32±7 years and a mean disease duration of 13±6.7 months were evaluated. The prevalence of patients with axial SpA who performed exercise was 44% (127). In patients with axial SpA practicing physical exercise statistically significant differences compared to those who did not perform physical exercise as to be found: increased presence of inflammatory bowel disease (5.5% vs 1.1%; p=0.04); lower ESR although within the normal range (10.2±11.1 vs 16.5±14.7; p=0.001) and more NSAIDs (92% vs 73%, p<0.01). There were no significant differences in the others parameters studied between the two groups. Conclusions: Less than half of our patients with early axial SpA exercisers at the time of diagnosis. The group of patients who performed regular exercise had a higher frequency of inflammatory bowel disease and greater use of NSAIDs, interestlingly. Disclosure of Interest: None declared